Adherence to the Dietary Approaches to Stop Hypertension (DASH) diet and risk of total and cause-specific mortality: results from the Golestan Cohort Study. (5th May 2019) - Mokhtari, Zeinab; Sharafkhah, Maryam; Poustchi, Hossein; Sepanlou, Sadaf G; Khoshnia, Masoud; Gharavi, Abdolsamad; Sohrabpour, Amir Ali; Sotoudeh, Masoud; Dawsey, Sanford M; Boffetta, Paolo; Abnet, Christian C; Kamangar, Farin; et al.
Abstract: Objective: To evaluate the association between adherence to the Dietary Approaches to Stop Hypertension (DASH) diet and overall and cause-specific mortality in the Golestan Cohort Study (GCS). Methods: A total of 50 045 participants aged 40 years or older were recruited from Golestan Province, Iran, from 2004 to 2008 and followed for a mean of 10.64 years. The DASH diet score was calculated for each individual based on food groups. The primary outcome measure was death from any cause. Results: During 517 326 person-years of follow-up, 6763 deaths were reported. After adjustment for potential confounders, DASH diet score was inversely associated with risk of death from all causes and cancers [hazard ratio (HR): 0.86; 95% confidence interval (CI): 0.75, 0.98; and HR: 0.65; 95% CI: 0.47, 0.90, respectively]. A higher DASH diet score was associated with lower risk of gastrointestinal cancer mortality in men (HR: 0.55; 95% CI: 0.30, 0.99). A greater adherence to DASH diet was also associated with lower other-cancer mortality in women (HR: 0.50; 95% CI: 0.24, 0.99). No association between DASH diet score and cardiovascular disease mortality was observed, except that those dying of cardiovascular disease were younger than 50 years of age and smokers. Conclusions: Our findings suggest that maintaining a diet similar to the DASH diet is independently associated with reducing the risk of total death, cancers, and especially gastrointestinal cancers in men.